Distillate Fuel Stability and Cleanliness 1981
DOI: 10.1520/stp28361s
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Ship Fuels

Abstract: A laboratory evaluation has been made of water-soluble biocides which might be effective in controlling microbial contamination in water-compensated fuel storage tanks on naval ships. Higher concentrations of biocides were generally required for control of sulfate-reducing bacteria in steel drums simulating ships' tanks than in test-tube scale assays. At least tenfold higher concentrations were necessary when biocide additions were made after, rather than before, bacterial growth had developed extensively. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Tanks in the platform jacket can also contain ballast water or be used for the storage of potable water and fuel oils (Crouch 1982). Neihof & May (1982) have reported that SRB predominated in water, sludge and diesel oil samples from over 40 fuel storage tanks using a seawater-compensated ballasting system. (2) Seawater is used for the hydrostatic testing of pipelines and can remain within the pipeline for several months.…”
Section: Distribution Of Sulphate-reducing Bacteriamentioning
confidence: 99%
“…Tanks in the platform jacket can also contain ballast water or be used for the storage of potable water and fuel oils (Crouch 1982). Neihof & May (1982) have reported that SRB predominated in water, sludge and diesel oil samples from over 40 fuel storage tanks using a seawater-compensated ballasting system. (2) Seawater is used for the hydrostatic testing of pipelines and can remain within the pipeline for several months.…”
Section: Distribution Of Sulphate-reducing Bacteriamentioning
confidence: 99%
“…cedures, C. resinae has now been shown to cause similar problems within the fuel systems of ships powered by gas turbines [5]. Growth of C. resinae and other micro-organisms occurs predominantly at the hydrocarbon-water interface in tanks where the fuel is displaced by seawater.…”
Section: Introductionmentioning
confidence: 99%
“…2). The delay in the initiation of growth by filamentous fungi until the pH of the aqueous phase was considerably more acidic than at the time of inoculation may suggest a role for yeasts as acidifying agents [4]. However, such a delay was also observed in pure cultures of the filamentous species in which aqueous phase pH did not alter before growth.…”
Section: Resultsmentioning
confidence: 99%
“…Filamentous fungi, in particular Ciadosporiurn resinae, have been implicated as the major organisms blocking fuel filters [2,3] but the development of other contaminating populations has been largely neglected. The action of Candida yeasts as primary contaminating agents has been suggested as essential before filamentous fungi can exploit the environment [4]. Such acid-producing alkali-tolerant yeasts are thought to change the value of the pH of the aqueous phase, allowing filamentous organisms to initiate growth.…”
Section: Introductionmentioning
confidence: 99%